Therapeutic Implications of Traditional Chinese Medicine in Clinically Relevant Diseases: Perspectives From microRNA-Modulated Apoptotic Signaling - Xu Q; Wu D; Tan J; Khan FA; Pandupuspitasari NS; Huang C (Drug Design, Development and Therapy)
Qinzheng Xu,1,* Di Wu,1,* Jiachen Tan,1,* Faheem Ahmed Khan,2,3 Nuruliarizki Shinta Pandupuspitasari,4,5 Chunjie Huang1 1School of Medicine, Nantong University, Nantong, 226001, People’s Republic of China; 2Research Center for Animal Husbandry, National Research and Innovation Agency, Jakarta Pusat, 10340, Indonesia; 3Stem Cell and Cancer Research, Semarang, 50223, Indonesia; 4Animal Science Department, Faculty of Animal and Agricultural Sciences, Universitas Diponegoro, Semarang, 50275, Indonesia; 5Food Sustainable Research Center (FORCE), Universitas Diponegoro, Semarang, 50275, Indonesia*These authors contributed equally to this workCorrespondence: Nuruliarizki Shinta Pandupuspitasari, Animal Science Department, Faculty of Animal and Agricultural Sciences, Universitas Diponegoro, Semarang 50275, Indonesia; Food Sustainable Research Center (FORCE), Universitas Diponegoro, Semarang, 50275, Indonesia, Email nuruliarizkishintapa@lecturer.undip.ac.id Chunjie Huang, School of Medicine, Nantong University, Nantong, 226001, People’s Republic of China, Email goodlife.huang@ntu.edu.cnAbstract: Traditional Chinese medicines (TCMs) have been employed as a potent therapeutic modality within Chinese cultural contexts to address a spectrum of diseases. MicroRNAs (miRNAs) are endogenous, non-coding RNA (ncRNA) molecules that regulate genetic expression via post-transcriptional mechanisms. By modulating miRNA expression, TCMs have been proven to confer protective benefits, notably by facilitating apoptosis induction. Thus, exploring the molecular mechanisms implicating miRNAs within TCMs could offer potential avenues for developing novel strategies to mitigate various lethal illnesses. In this study, we aim to provide a concise overview delineating the contemporary understanding of the functions of TCMs in miRNA-mediated apoptosis across malignant and non-malignant pathologies, including cancer, neurological disorders, and cardiovascular diseases. This review will furnish valuable insights concerning the clinical utilization of TCMs in treatment and prevention across a spectrum of clinically relevant diseases and serve as a catalyst for the innovation of novel therapeutic agents to address these pathologies.Keywords: traditional Chinese medicine, miRNAs, apoptosis, malignant and non-malignant pathologies, molecular basis of TCMs in disease